Revisitando a legitimidade ativa "ad causam" do processo coletivo: o pensamento sistemático aberto fundando novos horizontes para a atuação do indivíduo membro do grupo - SOUSA, Brahim Bitar de (Universidade Federal do Pará, 2018)
The Brazilian Procedural Science is experiencing a time of deep changes in the role of jurisdiction and legal protection models of the various rights and interests, individual and collective ones. In this scenario, this study has the main purpose to analyze the admissibility model of collective process, precisely the question of active legitimacy for the proposition and conduction of Class Actions in order to investigate more efficient and justified perspectives for the adequate provision of collective protection. In this regard, will be objected the current statement of provocative inability of the individual to the development of judicial activity in the collective way, guided by the hypothesis that this peremptory denial of active legitimacy is a legal dogmatic error linked to a classical conception of system, while a conception of system based on openness (on the Canaris's model) allows a judgment that includes the class member among the legitimated subjects to the collective process in general, ensuring greater effectiveness and giving prestige to the legal principles that guide collective protection.